Estrategias de inclusión para el fortalecimiento en la diversidad intercultural en estudiantes de educación básica. - Sanchin Chumap, Eva Marlene (2025)
This research analyzed the limited use of multicultural inclusion strategies to strengthen intercultural diversity among elementary school students at the "Otto Arosemena Gómez" Educational Unit in Quevedo, Los Ríos province. The objective of this study was to propose a pedagogical strategy that promotes respect, appreciation, and the experience of cultural diversity, based on the sociocultural contributions of Vygotsky, Freire's critical pedagogy, and Piaget's constructivism. The study adopted a qualitative approach with a non-experimental, cross-sectional, and descriptive-exploratory and provositive design. Semi-structured interviews were conducted with six teachers and direct observation was conducted with 39 seventh-grade students, using instruments validated by experts. The theoretical methods employed were analytical-synthetic, inductive-deductive, and historical-logical, which allowed the findings to be contextualized within conceptual and normative frameworks. The results showed that, although teachers recognize the importance of interculturality, its application in the classroom is limited by insufficient specialized training, the nonexistent use of ancestral languages, and inconsistent institutional support. Students, for their part, have a superficial understanding of cultural diversity and do not fully understand its educational and social value. Based on this diagnosis, the proposal "Multicultural Inclusion Strategies for Elementary School Students" was developed. This approach integrates learning projects with a multicultural approach, cultural narratives, collaborative activities, and school-community coordination, constituting a relevant pedagogical resource for strengthening intercultural diversity and fostering harmonious coexistence in the school context.